Soccer anatomy - Kirkendall, Donald T. (Human Kinetics, 2011)
Take an inside look at the world's most popular sport. Soccer Anatomy will show you how to elevate your game by increasing strength, speed, and agility for more accurate passes and powerful shots. Soccer Anatomy includes 79 exercises, each with step-by-step descriptions and full-color anatomical illustrations highlighting muscles in action. Soccer Anatomy goes beyond exercises by placing you on the pitch and in the game. Illustrations of the active muscles involved in kicking, heading, tackling, and diving show you how each exercise is fundamentally linked to soccer performance. From attacking to defending to goalkeeping, Soccer Anatomy will improve every aspect of your game. You'll learn how to modify exercises to target specific areas based on your style of play, personal needs, and goals. And you can prepare for competition by minimizing injuries using a system developed by FIFA's medical research program. Combining authoritative advice, expert instruction, and stunning four-color illustrations, Soccer Anatomy is truly an inside look at this one-of-a-kind sport. Whether you're a player, coach, or fan, if you're serious about soccer, this is one book you need to own.